159k views
23 votes
Simplify:
(i) 5√7 x 3√14

2 Answers

11 votes

Answer:

105
√(2)

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Given

5
√(7) × 3
√(14)

= 5 × 3 ×
√(7(14))

= 15 ×
√(98)

= 15 ×
√(49(2))

= 15 ×
√(49) ×
√(2)

= 15 × 7 ×
√(2)

= 105
√(2)

User Nicolas ABRIC
by
5.7k points
3 votes

5√7 × 3√14 = 5 × 3√(7 × 14)

= 15√98

= 105√2

User Piotr Pasieka
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.